(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2013)
The life and work of the mid-19th Century poet Emily Dickinson has attracted considerable attention in recent years from literary critics, biographers, and contemporary poets on both sides of the Atlantic. I suggest a number of possible reasons for renewed interest in this reclusive, intensive writer. I make a case (with reference to her seminal work) for her particular significance to modern psychology, and especially to my own discipline of existential-phenomenological therapy. I argue that her unique contribution is grounded in her attempts, via what may be thought of as ’a philosophical and philological probing’, to chart the metaphorical architecture of the brain, and to describe the experience of being a "divided self" – of fragmentation or splitting of the mind.